The AssistedDecisionm-Making (Capacity) Act 2015: Interrogating the guiding principles for a person with dementia. (September 2022) - Davidson, Hope
Abstract: Healthcare decision-making can present challenges for the person with dementia as many of the skills needed to navigate the decision-making process may be diminished or lost as a result of dementia. Currently in Ireland the law responds to this difficult dilemma by providing for a system of adult guardianship - and outside of that, a great deal of uncertainty. This is set to change when the Assisted Decision-Making Capacity Act (ADMCA) 2015 comes into force in the summer of 2022. The ADMCA aims to provide a modern statutory framework that supports decision-making by adults and enables them to retain the greatest amount of autonomy possible in situations where they lack or may shortly lack legal capacity. The Act aims to do this both through creating a set of guiding principles for decision-making and by the creation of formal decision-making agreements. This article aims to examine the guiding principles of the Act as they affect the person with dementia, and to assess the degree to which they will support and guide people with dementia and their healthcare professionals in making decisions. The guiding principles are of singular importance because they will govern any treatment decision by or for a person which is not the subject of a formal agreement. In interrogating the guiding principles of the Act the article seeks to identify ways in which the ADMCA differs from the equivalent legislation in England and Wales, the Mental Capacity Act (MCA) 2005. The MCA came into force in 2007 and therefore the discussion is informed by almost fifteen years operation of the MCA. The article will argue that not only is the ADMCA a huge step forward from the current position in Ireland but that a number of key differences between the MCA and the ADMCA mean that the ADMCA has the potential to be more empowering for the person with dementia.